Systematic review and meta-analysis of modular endoprosthesis and allograft-prosthetic composite reconstruction results after bone tumor resection - Vyrva, Oleg; Golovina, Yanina; Malyk, Roman; Golovina Оlga (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Introduction: in order to replace large post-resection defects of long bones, modular endoprostheses (ME), segmental bone allografts and allograft-prosthetic composite (APC) are predominantly used (a technique combining both methods). Objective: to conduct a comparative analysis of studies/papers (according to the literature data) as for using of modular endoprosthetics and allograft-prosthetic composite after bone tumor resection. Methods: we have done comparative statistical analysis of the literature data (44 studies) and a meta-analysis of the treatment results of patients with long bone malignant tumors using ME and APC (4 studies). Statistical processing (meta-analysis) of the data was carried out with certified Cochrane Collaboration software Review manager 5.3. Results: a total of 2840 patients were analyzed (comparative analysis). For the statistical analysis, specific criteria were selected: infectious complications, nonunion of allograft and recipient bone, bone fractures, structural fractures (mechanical complications), allograft resorption, functional result according to the MSTS. We have selected 4 comparative studies for functional results (by meta-analysis method) assessment. There are results of 2 techniques for femoral defect replacement: ME and APC. These studies were retrospective, included 157 patients. Conclusions: better functional results and less infection complications were observed at APC technique for proximal humerus replacement compare to ME. The results of both methods of comparative analysis for the proximal femur revealed the absence of hip head dislocation and a significant reduction an infection rates with allograft-prosthetic composite. As a result of the meta-analysis, it has been showed that APC has a statistically significant advantages of these functional results (MSTS score) over the tumor ME for proximal femur tumor surgery procedures.